Victimology Kekerasan Berbasis Gender (KBG): Analisis Faktor yang Mempengaruhi Kerentanan Korban KBG - Azka Yuliani Rahmanie; Bunga Aqila Zahra; Fatwa Wira Yudha; Muhamad Romdon Agnia (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Gender-Based Violence (GBV) is a significant social problem in Indonesia, where women and children are often victims. This study aims to analyze economic factors that increase vulnerability to GBV and evaluate the effectiveness of existing legal protection. The research method used is empirical legal with a qualitative approach, involving interviews, focus group discussions, and documentation studies. The results of the study indicate that poor economic conditions, patriarchal norms, and limited access to education and legal services contribute to high levels of vulnerability. Although there are laws that protect victims, such as Law No. 23 of 2004, its effectiveness is still in doubt due to the lack of socialization and understanding of the law in the community and law enforcement officers. Many victims do not report because of social stigma and lack of information about their rights. The researcher suggests that there are concrete steps in increasing legal socialization, providing integrated services for victims, and policy reform so that legal protection can be more effective and responsive to the needs of GBV victims, as well as to reduce the rate of violence.